2020PA Novel bispecific BCMAxCD3 T cell-engaging antibody that treat multiple myeloma (MM) with minimal cytokine secretion. (1st October 2019) - Li, Z; Li, Q; Zhang, G; Ma, X; Li, Z; Hu, X; Ouyang, K; Li, B; Liu, Z
Abstract: Background: B-cell maturation antigen ( BCMA) is a potential therapeutic target in treatment of patients with MM. BCMA is widely expressed at the surface of myeloma cells and induces proliferative signals. BCMA-directed BCMA antibody conjugated with toxin has recently demonstrated outstanding anti-tumor responses and acceptable tolerability in MM treatment, allowing patients to achieve deeper responses with minimally added toxicity. Methods: We used ELISA and FACS to verify AP163 can be combined with CD3/BCMA protein on the cell surface. We used the reporter gene method to verify that it induced T cell activation and target cell killing. In vivo, efficacy was studied in NCI-H929 and Raji xenograft models in female NPG mice. NPG mice were injected subcutaneously into the right dorsal flank with NCI-H929/Raji cells and human PBMC. Then the mice were treated with AP163 and tumor volume was measured twice/week. Cynomolgus monkeys were mainly used for toxicity testing. Intravenous administration is consistent with clinical administration. Its main toxicological target is the increase of cytokines and a series of adverse reactions. Results: we constructed AP163 which binds to BCMA-expressing cell lines. AP163 induced both types of cell crosslinking, followed by T cell activation, cytokine production, proliferation and redirected target cell killing, with EC50 values in the picomolar range. The affinities of AP163 with human and cynomolgus CD3 are comparable. In vitro, AP163 only induced minimal cytokine release in the presence of BCMA target. When administered to mice bearing human MM xenografts and human T cells, AP163 eradicated subcutaneous tumors in two xenograft models tested and significantly delayed tumor growth at doses as low as 0.04mg/kg. AP163 displayed a 9-h half-life in cynomolgus and was well tolerated in non-human primates, even at high doses up to 5 mg/kg. Conclusions: AP163 clears tumor cells in a BCMA+ and T-cell dependent manner in vitro and in vivo. Our preclinical data suggest that AP163 induces less cytokine secretion than a conventional bispecific in vitro, with reduction of tumor cell in vivo. AP163 is highly efficacious, safe and convenient for the treatment of patients with MM. Legal entity responsible for the study: National Engineering Laboratory of High Level Expression In Mammalian Cells. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.